Destellos culturales entre España y Estados Unidos a través de la prensa estadounidense (1945-1952) - Sagredo Santos, Antonia; Maestro Bäcksbacka, Javier (Revista Complutense de Historia de América, 2010)
Spanish-American cultural relations during the period between the end of WWII and the signature of the Military Alliance in 1953 were conditioned by the State Department’s policy towards Spain and the corresponding attitude of Franco-Spain. These cultural intercourses were reported in American periodicals, and this paper has mainly made use of these periodicals as its main research source. In spite of the almost unsurmountable difficulties to attain normalcy in cultural relations, steps were taken so that a number of Spaniards got in touch with American society, culture and values, and conversely, an increasing number of Americans, mainly students, visited Spain.